2009
DOI: 10.1111/j.1365-2753.2008.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electronic medical records on patient–doctor communication during consultation: a narrative literature review

Abstract: The use of EMR exerts both positive and negative impacts on physician-patient relationships. The negative impacts can be overcome by some simple means as well as better designs of EMR systems and medical education interventions. Physicians' everyday practices of integrating EMR use into the clinical encounter as well as better design of EMR systems and EMR and communication training may facilitate PDC in computerized settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
173
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(189 citation statements)
references
References 50 publications
6
173
0
1
Order By: Relevance
“…Though implementation of electronic health records (EHRs) has been shown to have positive effects in quality and cost of care, 1,2 concerns have arisen regarding the impact of EHR use on patient-physician relationships, [3][4][5] particularly the computer's negative influence on overall patient centeredness. 3,6,7 Combined with a national shortage of primary care physicians [8][9][10] and increasing physician burnout, 11 these concerns have sparked efforts to redistribute responsibilities in an expanded primary care team.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though implementation of electronic health records (EHRs) has been shown to have positive effects in quality and cost of care, 1,2 concerns have arisen regarding the impact of EHR use on patient-physician relationships, [3][4][5] particularly the computer's negative influence on overall patient centeredness. 3,6,7 Combined with a national shortage of primary care physicians [8][9][10] and increasing physician burnout, 11 these concerns have sparked efforts to redistribute responsibilities in an expanded primary care team.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 Combined with a national shortage of primary care physicians [8][9][10] and increasing physician burnout, 11 these concerns have sparked efforts to redistribute responsibilities in an expanded primary care team. 12,13 In particular, the role of medical assistants (MAs) and nurses have been expanded to include clinical scribing, also known as team documentation.…”
Section: Introductionmentioning
confidence: 99%
“…EHR implementation literature has consistently reported difficulties with the process such as high costs, lowered productivity, disruption to patient care, dissatisfaction among staff, and lack of training and support. [3][4][5][6] Analogous concerns were noted by EPs surveyed for this study. Any of these barriers could cause providers to fall short of being meaningful users of EHRs.…”
Section: Discussionmentioning
confidence: 88%
“…1,2 With regard to prior research on challenges to adopting and implementing an EHR, a precursor to meaningfully using the electronic records, reviews of literature on EHR use consistently report start-up and ongoing cost as the most frequent barrier to adoption. 3,4 With regard to barriers to implementation, providers report difficulties in workflow redesign, time to learn the system, negative views on how EHRs change patient-provider interactions, poor EHR function in the course of providing clinical care, and lack of training and support. The barriers seem consistent across providers whether the providers see predominantly publicly insured or commercially insured patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 A systematic review revealed that EMR use often had a positive impact on information exchange, but diminished patient-centeredness and patient rapport. 2 Both computer skills and behavioral style had the ability to overcome some of the negative influence that emerged. 2 Physicians might employ three different methods of sharing information using the EMR.…”
mentioning
confidence: 99%